2019
DOI: 10.21037/jtd.2019.06.42
|View full text |Cite
|
Sign up to set email alerts
|

The role of diet in the development and management of gastroesophageal reflux disease: why we feel the burn

Abstract: Gastroesophageal reflux disease (GERD) is a common esophageal disorder that is characterized by troublesome symptoms associated with increased esophageal acid exposure. Cornerstones of therapy include acid suppressive agents like proton pump inhibitors (PPI) and lifestyle modifications including dietary therapy, although the latter is not well defined. As concerns regarding long term PPI use continue to be explored, patients and providers are becoming increasingly interested in the role of diet in disease mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 48 publications
0
61
0
12
Order By: Relevance
“…A number of risk factors have been associated with esophageal cancers, especially the more prevalent esophageal squamous cell carcinoma, including smoking, alcohol consumption, consumption of high temperature beverages, genetics, and diet [119]. Specifically, diet appears to have both direct and indirect effects on the esophagus through cytokine signalling pathways and obesity [138][139][140].…”
Section: Esophageal Cancermentioning
confidence: 99%
“…A number of risk factors have been associated with esophageal cancers, especially the more prevalent esophageal squamous cell carcinoma, including smoking, alcohol consumption, consumption of high temperature beverages, genetics, and diet [119]. Specifically, diet appears to have both direct and indirect effects on the esophagus through cytokine signalling pathways and obesity [138][139][140].…”
Section: Esophageal Cancermentioning
confidence: 99%
“…[20][21][22][23][24] Dietary factors also contribute to GERD, including the size of meal and fat, protein and carbohydrate content leading to gastric distension, delayed emptying, and increased gastric content acidity, as well as the timing of meals. 25 Obesity has a significant role in the pathophysiology of GERD. Research from the Nurses' Health Study found a dose-dependent relationship between body mass index (BMI) and GERD.…”
Section: Anatomy and Pathophysiology Of Gerdmentioning
confidence: 99%
“…Caffeine, alcohol, nicotine, and many medications (e.g., benzodiazepines, calcium channel blockers, nitrates, B2 agonists, and xanthines) all contribute to GERD through relaxation of the LES 20–24 . Dietary factors also contribute to GERD, including the size of meal and fat, protein and carbohydrate content leading to gastric distension, delayed emptying, and increased gastric content acidity, as well as the timing of meals 25 …”
Section: Anatomy and Pathophysiology Of Gerdmentioning
confidence: 99%
“…There are some lifestyle changes that can reduce the intensity of symptoms, including smoking cessation, reduction of alcohol consumption, weight loss and particularly A retrospective study on the evaluation of the symptoms, medications and improvement of the quality of life of patients undergoing robotic surgery for gastroesophageal reflux disease SOFIA K. KONSTANTINIDOU 1 , PENELOPE KOSTARAS 2 , GEORGIOS-ELEFTHERIOS ANAGNOSTOPOULOS 2 , SOPHIA-LIBERTY MARKANTONIS 2 , VANGELIS KARALIS 2 and KONSTANTINOS KONSTANTINIDIS 3 the reduction of abdominal obesity, avoidance of fatty foods and coffee consumption, and avoidance of eating late-night meals (5,(8)(9)(10)(11)(12)(13)(14)(15)(16). Posture during night sleep also appears to have a significant role in the improvement of symptoms; a bed head higher than 15-20 cm appears the least effective (1).…”
Section: Introductionmentioning
confidence: 99%